The Influence of Sharia Perception, Price, Location, Value Creation and Brand Trust on Loyalty of Modern Supermarket Customers - Yoesoep Edhie Rachmad; Muhammad Rizki; Moh Gifari Sono; Sari Fitri; Endang Meilani (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
The purpose of this study is to ascertain how factors such as value creation, brand image, brand trust, sharia perceptions, price, and location impact customer loyalty in supermarkets. Moreover, to determine which elements have the greatest impact. In this study, 300 people were interviewed, mostly grocery customers. Use the purposive sampling approach. Multiple regression analysis is the method used for data analysis. The findings demonstrated that 55% of consumer loyalty in supermarkets is influenced by brand perception, value creation, brand image, brand trust, pricing, and location. Sharia perceptions are favorable when the sig. 886 value is more than 0.05. With a sig. 115 value > 0.05, value creation has a favorable impact. With a sig value of 000 < 0.05, brand image is positively impacted. With a sig value of 0.03 < 0.05, brand image has a favorable impact. With a sig value of 0.01 < 0.05, price has a positive influence, and location has a positive effect with a sig value of 0.00 < 0.05. Consumer loyalty to supermarkets is simultaneously influenced by value creation, brand image, brand trust, perception of Sharia, pricing, and location with a sig value of 0.00 < 0.05.